1988
DOI: 10.2307/3899573
|View full text |Cite
|
Sign up to set email alerts
|

Variability within a Native Stand of Blue Grama

Abstract: Considerable variability and patchiness have been observed within sites of native range dominated by blue grama [Botielow gra&z(H.B.K.) GrIffItha] range at the Central Plains Experhuental Range, Weld County, Colorado. Patches contalnhtg tall plants of blue grama with many seedstalks were interspersed with patches of short plants with few seedstalks. Differences in plant height were not entirely related to soil properties. Relative differences ln plant height among plants collected in the field were maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…We used plants which differed genetically with respect to potentially important morphological characters. Initial differences among our genotypes were significant and often large (1.5-6 fold); in their original study of the set of clones from which ours were drawn, McGinnies et al (1988) reported similar magnitudes of variation for numbers of culms (54-287 per plant), culm height (26-48 cm), plant weight (9-54 g), and basal diameter (8-17 cm). Though all grazing syndrome characters need not occur in the same plant, we found characters relating to plant stature (leaf height, culm height, culm number) tended to co-vary among genotypes; these are likely to be the characters that most directly influence tissue losses to grazing.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…We used plants which differed genetically with respect to potentially important morphological characters. Initial differences among our genotypes were significant and often large (1.5-6 fold); in their original study of the set of clones from which ours were drawn, McGinnies et al (1988) reported similar magnitudes of variation for numbers of culms (54-287 per plant), culm height (26-48 cm), plant weight (9-54 g), and basal diameter (8-17 cm). Though all grazing syndrome characters need not occur in the same plant, we found characters relating to plant stature (leaf height, culm height, culm number) tended to co-vary among genotypes; these are likely to be the characters that most directly influence tissue losses to grazing.…”
Section: Discussionmentioning
confidence: 61%
“…Each was subdivided into replicate clones, which were placed in a common garden at the CPER in 1982. Different genotypes maintained significantly different morphologies under these common garden conditions, suggesting a genetic basis (McGinnies et al 1988). …”
Section: Sources Of Materialsmentioning
confidence: 99%
See 3 more Smart Citations